Cupuaçu (Theobroma grandiflorum) residue and its potential application in the bioremediation of 17-Α-ethinylestradiol as a Pycnoporus sanguineus laccase inducer. Issue 6 (3rd July 2018) - Golveia, Jhéssica C. S.; Santiago, Mariângela F.; Sales, Paulo T. F.; Sartoratto, Adilson; Ponezi, Alexandre N.; Thomaz, Douglas V.; Gil, Eric de Souza; F. Bara, Maria Teresa
Abstract: Bioremediation is a strategy to mitigate environmental impacts of hazardous pollutants from anthropogenic sources. Natural byproducts, including agroindustrial wastes (AW) can be used to induce enzyme biosynthesis, leading up to enhancement of pollutants degradation process. Therefore, this study aimed to evaluate the use of cupuaçu, Theobroma grandiflorum AW as Pycnoporus sanguineus Laccase (Lac) inducer in order to promote 17-α-ethinylestradiol (EE2) bioremediation. The macro and micro-nutrients levels of cupuaçu AWs were evaluated in order to establish further correlations with enzymatic biosynthesis induction. The fungus was cultivated for 7 days in temperature of 28 ± 2 °C and agitation of 150 rpm. For bioremediation, Lac enzymatic extract was added to EE2 solution (10 µg mL −1 ) and the percentage of removal was evaluated by HPLC after 1–24 hr of reaction. At optimized conditions, the enzyme extract production was remarkably enhanced by adding only 1% (w/v) of cupuaçu AW. Lac activity reached 1642 U mL −1 on the 6th day of culture, which was higher than positive control (511 U mL −1 ). 86% of EE2 removal was reached after 4 hr, and after 8 hr of reaction, 96.5% was removed. Analysis by direct infusion in MS-ESI-TOF exhibited intermediary compounds formed by radical hydroxilation.